THE MUSIC ON DEVELOPING SELF-ESTEEM OF THE MAIN CHARACTER IN LONDON TOWN MOVIE: Musik membentuk sifat percaya diri karakter utama dalam film "London Town" - Ricky, Aldino (MEMACE: Jurnal Linguistik, Pendidikan Bahasa Indonesia, dan Asing, 2023)
Aldino Ricky (33190082), The Music on Developing Self-Esteem Main Character in London Town Movie. Movies and music are examples of literature as a medium for expressing and developing one's potential, capacity, talent, and skill. Movies and music have been investigated extensively in the literary world. One of the studies that have been done by academics examines on the impact or effect that literature, and particularly music, has on a person's sense of self-esteem. The writer chooses London Town movie as the media of analysis regarding the impact of music in developing self-esteem. In conducting this study, the writer uses qualitative descriptive method as the research method. In addition, the grand theory of analysis, the writer uses Cooper-smith’s self-esteem theory. The objectives of this study are to identify how music affects how the major characters' self-esteem develops in movies and to identify the type of self-esteem the main characters develop. The results of analysis are: First and foremost, music contributes to the improvement of the self-esteem of the main character through the acquisition of strong and significant behavior, virtue, and competence. Second, as a result of the influence of music, the main character gains a high level of self-esteem.